Genetic association of the activin A receptor gene (ACVR2A) and pre-eclampsia - Fitzpatrick, E.; Johnson, M.; Dyer, T.; Forrest, S.; Elliott, K.; Blangero, J.; Brennecke, S.; Moses, Eric (2009)
Pre-eclampsia is a common serious disorder of human pregnancy, which is associated with significant maternal and perinatal morbidity and mortality. The suspected aetiology of pre-eclampsia is complex, with susceptibility being attributable to multiple environmental factors and a large genetic component. Recently, we reported significant linkage to chromosome 2q22 in 34 Australian/New Zealand (Aust/NZ) pre-eclampsia/ eclampsia families, and activin A receptor type IIA (ACVR2A) was identified as a strong positional candidate gene at this locus. In an attempt to identify the putative risk variants, we have now comprehensively re-sequenced the entire coding region of the ACVR2A gene and the conserved non-coding sequences in a subset of 16 individuals from these families. We identified 45 single nucleotide polymorphisms (SNPs), with 9 being novel. These SNPs were genotyped in our total family sample of 480 individuals from 74 Aust/NZ pre-eclampsia families (including the original 34 genome-scanned families). Our best associations between ACVR2A polymorphisms and pre-eclampsia were for rs10497025 (P = 0.025), rs13430086 (P = 0.010) and three novel SNPs: LF004, LF013 and LF020 (all with P = 0.018). After correction for multiple hypothesis testing, none of these associations reached significance (P > 0.05). Based on these data, it remains unclear what role, if any, ACVR2A polymorphisms play in pre-eclampsia risk, at least in these Australian families. However, it would be premature to rule out this gene as significant associations between ACVR2A SNPs and pre-eclampsia have recently been reported in a large Norwegian (HUNT) population sample. © The Author 2009. Published by Oxford University Press on behalf of the European Society of Human Reproduction and Embryology. All rights reserved.